(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the interest of students in physical education classes in grades 7 and 8 at SMP Negeri 9 Kota Jambi. Student interest is measured through several indicators that influence interest, namely enjoyment, student interest, student involvement, and attention in learning. This study was conducted at SMP Negeri 9 Kota Jambi from May 20 to June 17, 2025. The data in this study aims to identify the level of student interest in participating in PJOK learning at SMP Negeri 9 Kota Jambi, particularly in grades 7 and 8. The literature review emphasizes that interest is influenced by internal factors, such as motivation and talent, as well as external factors, such as the role of teachers, facilities, and the school environment. The method used is quantitative descriptive with a survey technique. Data was collected through a questionnaire that had been tested for validity, with a total of 490 student respondents. The results showed that student interest was in the Good category (66.53%), with each indicator obtaining a percentage of 70%.